Immediate Postpartum Long-Acting Reversible Contraception: A Comparison Across Six Humanitarian Country Contexts - Gallagher, Meghan C.; Morris, Catherine N.; Fatima, Aisha; Daniel, Rebekah W.; Shire, Abdikani Hirsi; Sangwa, Bibiche Malilo Matala (Frontiers in Global Women's Health, 2021)
Postpartum family planning could prevent more than 30% of maternal deaths by effectively spacing births; this is particularly relevant in fragile contexts given that disproportionate maternal death occurs in countries affected by crises. In humanitarian settings, where accessing functional facilities is challenging with security risks that constrain movement, many women are unable to return for their 6-week postpartum visits and thus unable to receive FP counseling and adopt a method that suits their fertility intentions. Thus, IPPFP interventions tailored toward fragile contexts could contribute to healthy timing and spacing of pregnancy, particularly among postpartum women, and improve maternal and newborn health. In 2014, Save the Children integrated postpartum IUD services into its family planning package in emergency settings. In 2017 this expanded to include postpartum implant uptake as well, given updated WHO guidelines. Three countries (DRC, Somalia, Pakistan) opted for higher intensity programming for IPPFP. This involved training delivery-room providers on counselling and provision of IPPFP as well as training antenatal care nurses in counselling pregnant women on IPPFP options. Three control countries (Rwanda, Syria, Yemen) did not implement notable IPPFP interventions, though they monitored IPPFP via monthly service delivery data. Using service delivery data from 2016 – 2019, we examined trends in IPPFP uptake and compared countries with higher intensity IPPFP interventions to the control countries without. Tests of association were performed to assess the significance of these differences. In the country programs with higher intensity IPPFP interventions, IPPFP as a percentage of all deliveries was much higher overall during the July 2016 - December 2019 period. The IPPFP intervention had a significant impact on the overall proportion of women and girls who adopted an IUD or Implant within the first 48 hours of delivery, F(5, 246) = 179.47, p = <0.001. The mean percentage of IPPFP among all deliveries in intervention country programs was 10.01% as compared to 0.77% in control countries. Results suggest that providing IPPFP in fragile contexts is feasible and leads to increased demand and uptake when multipronged solutions focusing on provider training, community outreach, and service integration are applied.